Growth, Root Formation, and Nutrient Value of Triticale Plants Fertilized with Biosolids - Wendy Mercedes Rauw; Michael Bela Teglas; Sudeep Chandra; Matthew Lewis Forister (The Scientific World Journal)
Biosolids are utilized as nutrient rich fertilizer. Little material is available on benefits to forage crops resulting from fertilization with biosolids. This paper aimed to compare the effects of fertilization with biosolids versus commercial nitrogen fertilizer on growth, root formation, and nutrient value of triticale plants in a greenhouse experiment. Per treatment, five pots were seeded with five triticale seeds each. Treatments included a nonfertilized control, fertilization with 100, 200, 300, 400, and 500 ml biosolids per pot, and fertilization with a commercial nitrogen fertilizer at the recommended application rate and at double that rate. Biomass production, root length, root diameter, nitrogen, phosphorus, and potassium concentration were analyzed at harvest. Fertilization with biosolids increased triticale production (P<0.001); production was similar for the 100 to 400 mL treatments. Root length, nitrogen, and phosphorus concentration increased, and potassium concentration decreased linearly with application rate. At the recommended rate, biomass production was similar between fertilization with biosolids and commercial fertilizer. However, plants fertilized with commercial fertilizer had considerably longer roots (P<0.001), higher nitrogen concentration (P<0.05), and lower potassium concentration (P<0.01) than those fertilized with biosolids. Our results indicate that at the recommended application rate, biomass production was similar between fertilization with biosolids and with commercial nitrogen fertilizer, indicating the value of biosolids fertilization as a potential alternative.